2011
DOI: 10.1890/09-2006.1
|View full text |Cite
|
Sign up to set email alerts
|

Population regulation by enemies of the grass Brachypodium sylvaticum: demography in native and invaded ranges

Abstract: The enemy-release hypothesis (ERH) states that species become more successful in their introduced range than in their native range because they leave behind natural enemies in their native range and are thus "released" from enemy pressures in their introduced range. The ERH is popularly cited to explain the invasive properties of many species and is the underpinning of biological control. We tested the prediction that plant populations are more strongly regulated by natural enemies (herbivores and pathogens) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 32 publications
(43 reference statements)
0
33
0
Order By: Relevance
“…A correlate is that non-indigenous plant species that are potential hosts experience relatively fewer attacks from indigenous insect herbivores. The tendency for insects to be more directed than fungi in finding host trees may be one of the reasons for variable results from testing predictions of ERH (Agrawal and Kotanen, 2003;Parker and Hay, 2005;Lombardero et al, 2008;Carrillo-Gavilán et al, 2012;Roy et al, 2011). Another reason is that there can be differences among insect guilds.…”
Section: Discussionmentioning
confidence: 99%
“…A correlate is that non-indigenous plant species that are potential hosts experience relatively fewer attacks from indigenous insect herbivores. The tendency for insects to be more directed than fungi in finding host trees may be one of the reasons for variable results from testing predictions of ERH (Agrawal and Kotanen, 2003;Parker and Hay, 2005;Lombardero et al, 2008;Carrillo-Gavilán et al, 2012;Roy et al, 2011). Another reason is that there can be differences among insect guilds.…”
Section: Discussionmentioning
confidence: 99%
“…Enemy exclusion experiments provide the most accurate assessments of the extent to which plant enemies control the performance of exotic plants and reduce their invasiveness (Blaney & Kotanen ; DeWalt, Denslow & Ickes ; Dostál ; Roy et al . ). These experiments are, however, time‐consuming, and use of pesticides or exclosures may have confounding side effects.…”
Section: Methodsmentioning
confidence: 97%
“…Decreased enemy richness or damage may translate into increased demographic performance (DeWalt, Denslow & Ickes ; Roy et al . ) and thus promote the spread of exotic species and increase their impact on native communities (Mitchell & Power ; but see van Kleunen & Fischer ). Loss of herbivores and pathogens, however, is very often compensated for by new interactions with enemies in the colonized range (Mitchell et al .…”
Section: Introductionmentioning
confidence: 99%
“…Herbivores do not always have negative effects on species performance in their native range (Prior et al 2015) and only few studies tested if the observed differences in damage between ranges have an impact in regulating plant populations (DeWalt et al 2004;Williams et al 2010;Roy et al 2011). Theoretically, exotic plants that experience high herbivore attack in their native range are more likely to escape top-down regulation and become invasive in the introduced range than plant species that experience only low levels of herbivory in their native range.…”
Section: Introductionmentioning
confidence: 99%